2020
DOI: 10.1002/humu.24092
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of germline RPS20 mutation phenotype to include Diamond–Blackfan anemia

Abstract: Diamond-Blackfan anemia (DBA) is a ribosomopathy of variable expressivity and penetrance characterized by red cell aplasia, congenital anomalies, and predisposition to certain cancers, including early-onset colorectal cancer (CRC). DBA is primarily caused by a dominant mutation of a ribosomal protein (RP) gene, although approximately 20% of patients remain genetically uncharacterized despite exome sequencing and copy number analysis. Although somatic loss-of-function mutations in RP genes have been reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…In a similar fashion to the discovery of PPAP, a combination of linkage analysis and WES identified a truncating variant of RPS20 in association with MMR-proficient CRC in a four-generation family ( 88 , 95 ). Subsequent studies have since identified three RPS20 mutations in familial CRC cases ( 96 , 97 ) and two in Diamond-Blackfan anemia (DBA) patients ( 98 ). Available experience suggests that only a small fraction of FCCTX susceptibility genes have been discovered so far, and that private genes and mutations are common, strengthening the idea of the heterogeneous genetic background of FCCTX ( 94 , 99 ).…”
Section: From Single Genes To the Exome And Genomementioning
confidence: 99%
“…In a similar fashion to the discovery of PPAP, a combination of linkage analysis and WES identified a truncating variant of RPS20 in association with MMR-proficient CRC in a four-generation family ( 88 , 95 ). Subsequent studies have since identified three RPS20 mutations in familial CRC cases ( 96 , 97 ) and two in Diamond-Blackfan anemia (DBA) patients ( 98 ). Available experience suggests that only a small fraction of FCCTX susceptibility genes have been discovered so far, and that private genes and mutations are common, strengthening the idea of the heterogeneous genetic background of FCCTX ( 94 , 99 ).…”
Section: From Single Genes To the Exome And Genomementioning
confidence: 99%
“…They later had autoimmune GI manifestations that are not typical of DBA but have been reported. Notably, chronic colitis of unclear etiology has recently been described in two individuals with DBA found to have germline pathogenic variants in RPS20 ( Bhar et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients with DBA have autosomal dominant pathogenic germline variants in genes encoding ribosomal biogenesis proteins (small and large subunit components), with two X-linked recessive genes (GATA1 and TSR2) also causative of DBA (Bhar, et al 2020, Boria, et al 2010, Campagnoli , et al 2008, Draptchinskaia, et al 1999, Farrar, et al 2011, Gazda, et al 2012, Gripp, et al 2014, Landowski, et al 2013, Mirabello, et al 2014, Narla and Ebert 2010, Sankaran, et al 2012, Wang, et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the gene discovery rate has expanded exponentially (Ulirsch et al, 2018). To date, over 20 genes have been associated with DBA, with all but two of them encoding proteins of the small or large ribosomal subunits (RPSs, RPLs, respectively): RPS19, RPL5, RPL11, RPS26, RPL35A, RPS10, RPS17, RPS24, RPS7, RPS15A, RPS20, RPS27, RPS28, RPS29, RPL9, RPL15, RPL18, RPL26, RPL27, RPL31, RPL35 (Aubert et al, 2018;Bhar et al, 2020;Doherty et al, 2010;Draptchinskaia et al, 1999;Farrar et al, 2008Farrar et al, , 2014Gazda et al, 2006Gazda et al, , 2008Ikeda et al, 2017;Landowski et al, 2013;Lezzerini et al, 2020;Mirabello et al, 2014Mirabello et al, , 2017Sankaran et al, 2012;Wang et al, 2015). The first eight genes together comprise roughly 50% of DBA cases.…”
Section: Introductionmentioning
confidence: 99%